Biodiversity effects of ecosystem engineers are stronger on more complex ecosystem processes. Issue 9 (1st September 2013) - Caliman, Adriano; Carneiro, Luciana S.; Leal, João J. F.; Farjalla, Vinicius F.; Bozelli, Reinaldo L.; Esteves, Francisco A.
Abstract : The relative importance of species richness and identity for the diversity–function relationship remains controversial. We mechanistically explored the potential contribution of ecosystem processes complexity (EPC; i.e., the number of pathways and mechanisms through which an ecosystem process can be directly and/or indirectly affected by species and/or their interactions) to the resolution of this controversy. We hypothesized that the complementarity effects of biodiversity will be stronger and that the diversity–function relationship will be more dependent on species richness as the EPC increases. Using a benthic bioturbator community as a model system we tested these predictions across ecosystem processes that could be ordered according to their complexity (suspended material flux < PO4 ‐P flux < NH4 ‐N flux < bacterioplankton production). Consistent with our predictions, species richness explained an increasing proportion of data variation as EPC increased, whereas the contrary was observed for species composition. Nontransgressive overyielding was not affected by EPC, but the magnitude of transgressive overyielding increased significantly with EPC, indicating that complementarity may be stronger as EPC increases. Our results highlight the importance of considering the interactive role of the characteristics of ecosystem processes in our theoretical understanding of the diversity–function relationship and its underlying mechanisms.